2018
DOI: 10.1080/00222895.2018.1425661
|View full text |Cite
|
Sign up to set email alerts
|

Movement Speed and Accuracy in Space and Time: The Complementarity of Error Distributions

Abstract: Movement speed-accuracy trade-off is a function of the space-time constraints of the task. We investigated the space-time account of Hancock and Newell (1985) and the hypothesis of complementarity between the four moments of the error distribution in space and time. Twelve participants performed 15 conditions in a line drawing task composed of different spatial (10, 20, and 30 cm) and temporal (250 to 2,500 ms) criteria. The results showed that all moments of distributions changed systematically between condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…The only way to understand the individual SAT relation would be by considering also the other moments of both spatial and temporal errors. Indeed, this was what Pacheco et al (13) demonstrated (see also (14)).…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…The only way to understand the individual SAT relation would be by considering also the other moments of both spatial and temporal errors. Indeed, this was what Pacheco et al (13) demonstrated (see also (14)).…”
Section: Introductionsupporting
confidence: 53%
“…Interestingly, its underlying processes and influential factors are far from being totally unraveled. In the present manuscript, we encompassed the views from Guiard and Rioul (5) and Hancock and Newell (6) to understand the individual intrinsic tendencies in SAT (see also (13)). A main issue is that such tendencies would not be easy to identify if they were simply a "bias" due to recent experiences (transient changes).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Provided the unique case where velocity is free to vary, the timing of release would determine the success of each throw (see also Cohen and Sternad, 2012; Zhang et al, 2018). This could have modified the expected increased-velocity-increased-variability relation (see Pacheco et al, 2019).…”
Section: Investigating Skill Acquisition (Change) As Searchmentioning
confidence: 97%